Membangun Aplikasi Game Interaktif Belajar Berhitung dan Mewarnai Untuk Anak TK - Mulia Rahmayu; Yunita Yunita (Universitas Bina Sarana Informatika, 2017)
ABSTRACTKids age 4-6 years is reaching maturity sensory and motor, this situation is a strategic time to introduce arithmetic and coloring. Teaches counting and coloring in a different way children with adults, a child's world is playing therefore create an atmosphere of learning while playing a fun and involving all the senses of children. Educational game is expected to improve the thinking ability of children in the learning process, that educational games are very useful in the field of education. System development methods that I use in making application interactive game to learn to count and this coloring is Multimedia Development Life Cycle (MDLC). Interactive game application is expected to provide facilities for children to learn to count and coloring so kids do not feel bored while studying because coupled with the element of the game. Keywords: Numeracy Coloring, Game, MDLC